Experimental Research on the Influence of Lens Cleaning Products, on Their Hardness - Beatrice Daniela TUDOR; Iustina BĂBUȘANU (The Annals of “Dunarea de Jos” University of Galati. Fascicle IX, Metallurgy and Materials Science)
The paper presents a study on the influence of optical lens cleaning products for vision correction on their hardness. The lenses under study were previously cleaned repeatedly with different cleaning products, namely, special eyeglass wipes and liquid detergent. The research was carried out on a group of lenses with and without protection, of different thicknesses and diopters.